Union, border effects, and market integration in Britain - Daniel Cassidy; Nick Hanley (European Historical Economics Society (EHES), 2022)
The Act of Union (1707) unified England and Scotland politically and economically, formally establishing the United Kingdom of Great Britain, and a customs union throughout the island of Britain. In this paper, we examine the impact of union on British market integration using wheat prices from a sample of English and Scottish markets. We estimate a coefficient of variation and a dynamic factor model to examine the evolution of price convergence and market efficiency across English and Scottish markets from the 1640s to the mid-eighteenth century. Our results suggest that union strongly influenced price convergence but had little impact on market efficiency. There was an immediate sharp increase in the level of price convergence across British markets following the union, suggesting that the elimination of tariffs and other trade frictions was a strong driver of price convergence. To formally test the impact of union on price convergence, we estimate border effects which show the impact of the pre-union border on price gaps between English and Scottish markets. The results suggest that the customs union strongly influenced price convergence, lowering the average price gap by 16%, and implying a pre-union border width of 160-162km.
Keywords: F15; N13; P45; 330; Customs Union; Market Integration; Prices